The Role Of Computer Assisted Audit Techniques, Professional Skeptism And Remote Auditing On Quality Of Audit In Public Accountant Office - Yoesoep Edhie Rachmad; Hedar Rusman; Samuel PD Anantadjaya; Moch Arif Hernawan; Diksi Metris (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aimed to test hypotheses and produce empirical evidence about the effect of remote auditing, computer assisted audit techniques, and professional skepticism on audit quality. The data research were gathered using a questionnaires distributed to 100 external auditors working at public accountant firm in DKI Jakarta. The research sample was determined using the purposive sampling. Data were analyzed using IBM SPSS 26 software. The results toward the data showed that remote auditing have a positive effect on audit quality, computer assisted audit techniques have a positive effect on audit quality, and professional skepticism have a positive effect on audit quality. Meanwhile, remote auditing, computer assisted audit techniques, and professional skepticism simultaneously effect on audit quality.